The impact of fiscal policy and inflation on national saving. A comment - ROSSI, N. (PSL Quarterly Review, 2013)
The increasing concern about the sustainability of current fiscal policies in Italy has led to a number of attempts in recent years to assess the Ricardian Equivalence Proposition. What is striking is that different authors have produced mixed, if not contradictory, evidence based largely on the same information. The present work highlights a particular work by Modigliani, Jappelli and Pagan (1985), to show that what appears to be contradictory evidence is largely the result of an incorrect treatment of dynamics. The author’s conclusions provide a warning against the danger of testing micro-hypotheses and consequently deriving policy prescriptions on the ground of an incorrect application of econometric tools to aggregate data. JEL: E31, E62